Chronic alcohol use and first symptomatic epileptic seizures. Issue 5 (1st November 2002) - Leone, M; Tonini, C; Bogliun, G; Monaco, F; Mutani, R; Bottacchi, E; Gambaro, P; Rocci, E; Tassinari, T; Cavestro, C; Beghi, E
Abstract : Objective: To establish whether chronic alcoholism and alcohol consumption are risk factors for developing a first symptomatic epileptic seizure. Methods: Multicentre case-control study of 293 patients (160 men, 133 women) with a first seizure symptomatic (either acute or remote) of head trauma, stroke, or brain tumour, matched to 444 hospital controls for centre, sex, age (±5 years), and underlying pathology. Results: The risk of first seizure in alcoholics was no higher than in non-alcoholics for men (odds ratio 1.2, 95% confidence interval 0.4 to 3.2) or women (1.5, 0.1 to 54.4). The odds ratio (both sexes) was 1.2 (0.8 to 1.7) for an average intake of absolute alcohol of 1–25 g/day, 0.9 (0.5 to 1.5) for 26–50 g/day, 1.6 (0.8 to 3.0) for 51–100 g/day, and 1.4 (0.5 to 3.5) for >100 g/day. Conclusions: We found no evidence of an association between alcohol use or alcoholism and a first symptomatic seizure.